A novel autosomal recessive lipodystrophy syndrome due to homozygous LMNA variant. Issue 6 (19th December 2019) - Patni, Nivedita; Hatab, Sarah; Xing, Chao; Zhou, Zhengyang; Quittner, Claudia; Garg, Abhimanyu
Abstract : Background: Despite major advances in understanding the molecular basis of various genetic lipodystrophy syndromes, some rare patients still remain unexplained. Cases: We report a novel autosomal recessive lipodystrophy affecting two sisters aged 17 and 19 years and characterised by early onset intellectual disability, and subsequent development of near-generalised loss of subcutaneous fat with diabetes mellitus, extreme hypertriglyceridemia, hepatic steatosis, short stature, clinodactyly, joint contractures, leiomyoma of uterus and cataracts in childhood. The lipodystrophy was more pronounced in the upper and lower extremities, and there was no associated muscular hypertrophy. Using whole exome sequencing in this consanguineous Hispanic pedigree, we report disease-causing homozygous p.Arg545His LMNA variant in the affected subjects, and confirm the lack of pathogenic variants in other known lipodystrophy genes. The mother and a younger brother were both heterozygous for p.Arg545His LMNA variant and were overweight with acanthosis nigricans without any evidence of lipodystrophy. Our patients are distinct from previously reported autosomal recessive lipodystrophy syndromes and have no overlap with other autosomal recessive laminopathies, including mandibuloacral dysplasia, Emery-Dreifuss muscular dystrophy and Charcot-Marie-Tooth neuropathy. Conclusion: Our report of this unusual familial generalised lipodystrophy syndrome adds to the pleiotropy associated with biallelic autosomal recessive LMNA variants.